Can Harry Potter still put a spell on us in a second language? An fMRI study on reading emotion-laden literature in late bilinguals. (February 2015) - Hsu, Chun-Ting; Jacobs, Arthur M.; Conrad, Markus
Abstract: In this fMRI study we contrasted emotional responses to literary reading in late bilinguals' first or second language. German participants with adequate English proficiency in their second language (L2) English read short text passages from Harry Potter books characterized by a "negative" or "positive" versus "neutral" emotional valence manipulation. Previous studies have suggested that given sufficient L2 proficiency, neural substrates involved in L1 versus L2 do not differ (Fabbro, 2001). On the other hand, the question of attenuated emotionality of L2 language processing is still an open debate (see Conrad, Recio, & Jacobs, 2011). Our results revealed a set of neural structures involved in the processing of emotion-laden literature, including emotion-related amygdala and a set of lateral prefrontal, anterior temporal, and temporo-parietal regions associated with discourse comprehension, high-level semantic integration, and Theory-of-Mind processing. Yet, consistent with post-scan emotion ratings of text passages, factorial fMRI analyses revealed stronger hemodynamic responses to "happy" than to "neutral" in bilateral amygdala and the left precentral cortex that were restricted to L1 reading. Furthermore, multivariate pattern analyses (MVPA) demonstrated better classifiability of differential patterns of brain activity elicited by passages of different emotional content in L1 than in L2 for the whole brain level. Overall, our results suggest that reading emotion-laden texts in our native language provides a stronger and more differentiated emotional experience than reading in a second language.